Hydrothermal treatment of eucalyptus sawdust for a forest biorefinery - Rangel M., Jesús (2016)
The aim of this study was to optimize the hydrothermal treatments conditions to obtain different products in the extraction of hemicelluloses from eucalyptus sawdust originated in carpenters and sawmills. Raw material was sawdust from 12-50years-old Eucalyptus rostrata, grandis, and saligina. A 23 Factorial Design was initially applied to verify the influence of the time of treatment (30, 45 and 60 min), temperature(120, 150 and 180°C) and liquid / solid ratio (5, 10, 15). This last variable was not significant. A Central Composite Face-Centered Design was used for the optimizations, varying time (20, 30 and 40 min) and temperature (170, 180 and190°C). Temperature was the most influential factor. Extractives can be removed in a first step at 120ºC for 20 min. The highest extraction of hemicelluloses (mainly as sugars) took place at 20 min and 190°C, whereas the maximum extraction of carbohydrates as oligomers was obtained at 40 minutes and about 170ºC.